EGF receptor tyrosine kinase inhibitors in the treatment of brain metastases from non-small-cell lung cancer. Issue 11 (November 2012) - Bartolotti, Marco; Franceschi, Enrico; Brandes, Alba Ariela
The incidence of brain metastasis (BM) is high in patients with non-small-cell lung cancer. Available standard therapeutic options, such as whole-brain radiation therapy and systemic chemotherapy, provide a slight improvement in local control, overall survival and symptom relief. Novel agents, such as EGF receptor (EGFR) tyrosine kinase inhibitors (TKIs), have now been included in standard non-small-cell lung cancer treatments. In a small subset of patients harboring EGFR -activating mutations, erlotinib and gefitinib administration was followed by a response rate of 70–80%, and a longer progression-free and overall survival than those obtained with standard chemotherapeutic regimens. However, since most of the larger studies on these agents have excluded BM patients from their series, few prospective data are available on the efficacy of these agents in this setting. In recent years, however, several authors have reported a growing number of cases of partial and complete response in BM patients treated with EGFR TKIs. Data from retrospective series and Phase II studies also suggest that a response can be obtained using EGFR TKI treatment for patients with BM, especially those harboring EGFR mutations.